Recommendations for the design of grouped headed studs. Issue 2 (May 2017) - Spremic, Milan; Markovic, Zlatko; Veljkovic, Milan
Abstract: Grouped headed studs may be successfully utilized to achieve the longitudinal shear connection between prefabricated slabs and steel beams. The behaviour of the studs and the ultimate resistance of the group were analysed using the results of experimental push tests and by employing advanced FE analyses. Different arrangements of studs in the group were investigated, focusing on minimal distance between the studs. It is demonstrated that the full shear resistance of a group of headed studs is achieved even when the distances between the studs are less than the minimum requirement according to EN 1994‐1‐1. Concrete class C30/37 is the minimum that should be used. Furthermore, the paper presents a new model for calculating the shear resistance of grouped headed studs. The proposed design model is based on an equivalent stud diameter and can be used for various arrangements of headed studs in a group. The shear resistance formula and the requirements for ductility are consistent with the existing Eurocodes. Fatigue loading is not considered in this paper, so the proposed recommendations are valid for buildings including multi‐storey car parks.